Like Terms or Similar Terms:
Like terms are the terms which have the same variables with same exponent for each variable.
7x, 3x, - 4x
Unlike Terms or Dissimilar Terms:
Unlike terms are the terms which have same variables or different variables.
If they have same variables, the exponents will not be same.
9x2, 5xy, - 4xy2, y, 6
To do addition and subtraction of algebraic expression, we have to know the difference between like and unlike terms.
Because, in algebraic expression, we can do addition and subtraction only on like terms not on unlike terms.
Adding or subtracting polynomials is nothing but combining the like terms. Here we give step by step explanation for adding and subtracting polynomials.
Let us look at some examples to have better understanding on addition and subtraction of algebraic expression with like terms.
Example 1 :
3x3 + x2 - 2 and 2x2 + 5x + 5
First we have to arrange the like terms column wise and add them.
Observe the important points related to the above work.
1. We have written the term 2x2 of the second polynomial below the corresponding term x2 of the first polynomial.
(Because x2 and 2x2 are like terms and they can be combined)
2. Similarly, the constant term +5 is placed below the constant term – 2.
3. Since the term x in the first polynomial and the term x3 in the second polynomial do not exist, their respective places have been left blank to facilitate the process of addition. Or, for the non existing terms, we annex the terms with zero coefficients.
Example 2 :
Find out the sum of the polynomials :
3x - y, 2y - 2x, and x + y.
We can find out the sum of the given polynomials using either column method of addition or row method of addition as explained below.
Once they are written in the above methods, we have to combine the like terms.
Example 3 :
Subtract 5xy from 8xy.
Example 4 :
Subtract (3c + 7d2) from (5c - d2).
Alternatively, this can also be done as :
(5c - d2) - (3c + 7d2) = 5c - d2 - 3c - 7d2
= (5c - 3c) + (-d2 - 7d2)
= 2c + (-8d2)
= 2c - 8d2
Example 5 :
Subtract (2x2 + 2y2 - 6) from (3x2 - 7y2 + 9)
Example 6 :
(7p3 + 4p2- 8p + 1 ) and (3p3- 5p2- 10p + 5)
Step 1 :
The two given polynomials are already in the arranged form.So we can leave it as it is.
= (7p3 + 4p2- 8p + 1 ) and (3p3- 5p2- 10p + 5)
Step 2 :
Now we have to write the like terms together starting from the highest power to lowest power.
= 7p3 + 3p3 + 4p2- 5p2- 8p - 10p + 1 + 5
So, the final answer is
10p3- 1p2- 18p + 6.
Example 7 :
(2x3 + 5x2 - 2x + 7) and (x3 + 4x2 - x + 6)
= (2x3 + 5x2 - 2x + 7) + (x3 + 4x2 - x + 6)
= 2x3 + 5x2 - 2x + 7 + x3 + 4x2 - x + 6
= 2x3 + x3 + 5x2 + 4x2 - 2x - x + 7 + 6
= 3x3 + 9x2 - 3x + 13
Example 8 :
(3x3 - 2x2 - x + 4) and (2x3 + 7x2 - 3x - 3)
= (3x3 - 2x2 - x + 4) + (2x3 + 7x2 - 3x - 3)
= 3x3 - 2x2 - x + 4 + 2x3 + 7x2 - 3 x - 3
= 3x3 + 2x3 - 2x2 + 7x2 - x - 3x + 4 - 3
= 5x3 + 5x2 - 4x + 1
Example 9 :
2(x3 - x2 + 6x - 2) and (5x6 + 7x5 - 3x - 3)
= 2(x3 - x2 + 6x - 2) + (5x6 + 7x5 - 3x - 3)
= 2x3 - 2x2 + 12x - 4 + 5x6 + 7x5 - 3x - 3
= 5x6 + 7x5 + 2x3 - 2x2 + 12x - 3x - 4 - 3
= 5x6 + 7x6 + 2x3 - 2x2 + 9x - 7
Example 10 :
-1(x6 + x3 + 6x2 - 2) and 2(5x6 + 7x5 - 3x - 3)
= -1(x6 + x3 + 6x2 - 2) + 2(5x6 + 7x5 - 3x - 3)
= -x6 - x3 - 6x2 + 2 + 10x6 + 14x5 - 6x - 6
= -x6 + 10x6 + 14x5 - x3 - 6x2 - 6x + 2 - 6
= 9x6 + 14x5 - x3 - 6x2 - 6x - 4
Example 11 :
5(5x6 + 2x3 - 6x2 - 2) + 6(-3x6 + 2x5 + 2x + 1)
= 5(5x6 + 2x3 - 6x2 - 2) + 6(-3x6 + 2x5 + 2x + 1)
= 25x6 + 10x3 - 30x2 - 10 -18x6 + 12x5 + 12x + 6
= 25x6 -18x6 + 12x5 + 10x3 - 30x2 + 12x -10 + 6
= 7x6 + 12x5 + 10x3 - 30x2 + 12x - 4
Example 12 :
-2(2x4 - 2x3 - x2 + 5) and 3(2x4 - 2x2 - 3)
= -2(2x4 - 2x3 - x2 + 5) + 3(2x4 - 2x2 - 3)
= -4x4 + 4x3 + 2x2 -10 + 6x4 - 6x2 - 9
= -4x4 + 6x4 + 4x3 + 2x2 - 6x2 -10 - 9
= 2x4 + 4x3 - 4x2 - 19
Example 13 :
5(x4 - x3 + 5) and 2(x4 - 5x2 - 7)
= 5(x4 - x3 + 5) + 2(x4 - 5x2 - 7)
= 5x4 - 5x3 + 25 + 2x4 - 10x2 - 14
= 5x4 + 2x4 - 5x3 - 10x2 + 25 - 14
= 7x4 - 5x3 - 10x2 + 11
Example 14 :
3(6x4 - 2x3 - 3) and 2(2x4 - x2 - 8)
= 3(6x4 - 2x3 - 3) + 2(2x4 - x2 - 8)
= 18x4 - 6x3 - 9 + 4x4 - 2x2 - 16
= 18x4 + 4x4 - 6x3 - 2x2 - 9 - 16
= 22x4 - 6x3 -2x2 - 25
Example 15 :
(6x7 - 2x6 - 3x3 + 2x2) and 2(2x4 + 5x7 + 3x6 + x3 + x2)
= (6x7 - 2x6 - 3x3 + 2x2) + 2(2x4 + 5x7 + 3x6 + x3 + x2)
= 6x7 - 2x6 - 3x3 + 2x2 + 4x4 + 10x7 + 6x6 + 2x3 + 2x2
= 6x7 + 10x7- 2x6 + 6x6 + 4x4 - 3x3 + 2x3 + 2x2 + 2x2
= 16x7 + 4x6 + 4x4 - x3 + 4x2
Example 16 :
(x7 - 3x6 - 2x3 + x2) and 5(3x4 + 15x7 + 4x6 + 2x3 + 6x2)
= (x7 - 3x6 - 2x3 + x2) + 5(3x4 + 15x7 + 4x6 + 2x3 + 6x2)
= x7 - 3x6 - 2x3 + x2 + 15x4 + 75x7 + 20x6 + 10x3 + 30x2
= x7 + 75x7- 3x6 + 20x6 - 2x3 + 10x3 + x2 + 30x2
= 76x7 + 17x6 + 8x3 + 31x2
Apart from the stuff given above, if you need any other stuff in math, please use our google custom search here.
Kindly mail your feedback to firstname.lastname@example.org
We always appreciate your feedback.